Mendelian randomization: Estimation of inpatient hospital costs attributable to obesity - Katherine Dick; John E. Schneider; Andrew Harvey Briggs; Pascal Lecomte; Stephane A. Regnier; Michael Lean (Health Economics Review, 2021)
Background: Mendelian Randomization is a type of instrumental variable (IV) analysis that uses inherited genetic variants as instruments to estimate causal effects attributable to genetic factors. This study aims to estimate the impact of obesity on annual inpatient healthcare costs in the UK using linked data from the UK Biobank and Hospital Episode Statistics (HES). Methods: UK Biobank data for 482,127 subjects was linked with HES inpatient admission records, and costs were assigned to episodes of care. A two-stage least squares (TSLS) IV model and a TSLS two-part cost model were compared to a naïve regression of inpatient healthcare costs on body mass index (BMI). Results: The naïve analysis of annual cost on continuous BMI predicted an annual cost of 21.61 [95% CI 20.33 - 22.89] greater cost per unit increase in BMI. The TSLS IV model predicted an annual cost of 14.36 [95% CI 0.31 - 28.42] greater cost per unit increase in BMI. Modelled with a binary obesity variable, the naïve analysis predicted that obese subjects incurred 205.53 [95% CI 191.45 - 219.60] greater costs than non-obese subjects. The TSLS model predicted a cost 201.58 [95% CI 4.32 - 398.84] greater for obese subjects compared to non-obese subjects. Conclusions: The IV models provide evidence for a causal relationship between obesity and higher inpatient healthcare costs. Compared to the naïve models, the binary IV model found a slightly smaller marginal effect of obesity, and the continuous IV model found a slightly smaller marginal effect of a single unit increase in BMI.
Keywords: 330; Mendelian randomization; Obesity; Instrumental variables; Genetics; Economics; Healthcare utilization